Report on the earthquake in Turkey: Field observation on healthcare services and ethical challenges - Değer, Mehmet Sait; Özdinç, Ahmet (Bangladesh Journal of Medical Science, 2023)
On February 6, 2023, an earthquake with a magnitude of 7.7 m occurred in Turkey, centered in the Pazarcık district of Kahramanmaraş province, followed nine hours later by another earthquake with a magnitude of 7.6 m, centered in the Elbistan district of Kahramanmaraş province. In the earthquakes, 45,000 people died, and more than 100,000 were injured. During the earthquake search-and-rescue personnel, emergency responders, and volunteers worked in the field. Disasters that suddenly affect large masses of people create many issues related to medical ethics. Likewise, difficulties caused by limited resources lead to issues related to beneficence, non-maleficence, autonomy and justice. This is a descriptive research study based on the field observations of researchers who were actually in the disaster area after the earthquakes, as well as an analysis of and observations related to the news, information and reports published. This study draws attention to ensuring the participation of society in the fight against and response to disasters. In addition, ethical guidelines for healthcare providers in disasters should be prepared and integrated into national disaster plans. Turkey’s earthquake experience will provide essential information for decision-makers and practitioners regarding the extent of the area impacted and the scope of the affected population. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page :815-826